2010
DOI: 10.1007/s11738-010-0551-5
|View full text |Cite
|
Sign up to set email alerts
|

The differing responses of two Arabidopsis ecotypes to ammonium are modulated by the photoperiod regime

Abstract: Responses to excessive ammonium (NH 4 ? ) were compared between two Arabidopsis ecotypes (Col-0, JA22) with respect to different photoperiods in hydroponics. In this study, we showed that external extra NH 4 ? led to severe growth suppression, accumulations of free NH 4 ? and amino acids and increased the activities of glutamine synthetase (GS) and glutamate dehydrogenase (GDH) in shoots of the two Arabidopsis ecotypes. However, the levels of free NH 4 ? and total amino acids increased, whereas the activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…In previous studies, the most obvious inhibition caused by NH 4 + nutrition was reflected by the reduced plant biomass (Li et al , Wang et al , Wang et al ). In the present study, in NH 4 + ‐sensitive AK58, NH 4 + ‐fed plants produced 28.5 and 22.1% lower plant dry biomass and leaf areas, respectively than NO 3 − ‐fed plants.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, the most obvious inhibition caused by NH 4 + nutrition was reflected by the reduced plant biomass (Li et al , Wang et al , Wang et al ). In the present study, in NH 4 + ‐sensitive AK58, NH 4 + ‐fed plants produced 28.5 and 22.1% lower plant dry biomass and leaf areas, respectively than NO 3 − ‐fed plants.…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with the reports of Liu et al (2013) andP erez-Tienda et al (2014), who showed that the N metabolisms in mycorrhizal roots were significantly changed. Li et al (2011) , and other nutrients from the soil and transport these nutrients to different tissues using a variety of transporters. For example, AMT protein family members transport NH 4 þ , and NRT protein family members transport NO 3 -.…”
Section: Nitrogen Accumulation and Metabolic Level In Response To P mentioning
confidence: 99%
“…Nevertheless, NH 4 + frequently reaches levels in soils that affect plant growth negatively. These negative effects manifest in stunted root growth, yield depression, and chlorosis of leaves Balkos et al 2010;Li et al 2011b). However, higher plants display widely differing responses to NH 4 + nutrition (Marschner 1995) and, accordingly, can be divided into tolerant and sensitive species .…”
Section: Introductionmentioning
confidence: 99%